Laundry Detergent Compatibility of Papain Like Protease Purified From Piper Betel Leaves - Mousami Shankar, A; G.V.D. Sirisha, Dr; K. Vijaya Rachel, Dr (International Journal of Engineering and Technology, 2018)
Enzymes have wide applications in detergent industry from early 1900â€™s. Mostly, clothes are soiled by protein based grime. Most of the detergents have either amylase / protease. Various sources were scrutinized for potent protease activity and Betel leaves were selected, the enzyme was then isolated, purified to homogeneity by ammonium sulphate precipitation, DEAE-Cellulose and gel permeation chromatographic techniques. The enzyme was monomeric in nature with a molecular mass of 38kDa as determined by native PAGE and SDS-PAGE. The enzyme shows maximum activity at 60oC and pH 4.0. The Km and Vmax of the enzyme were 4x10-3M and 54Âµmol/min/mg respectively. The enzyme was categorically inhibited by PCMB and iodo-acetamide suggesting it to have papain like nature. The stability of the enzyme is assessed over the stretch of alkaline pH and temperature. This evaluation validates the stability of the enzyme and its use in detergent formulations. It was evident that after adding the enzyme preparation the stains (tea, chocolate, blood) were removed much better than that of the controls, which affirms that papain like enzyme from betel leaves, enhances detergent activity.Â Â